The relationship between career growth and organizational commitment among employees at Pejabat Daerah Samarahan, Sarawak / Mohd Sharul Rusyaidi Rosli - Rosli, Mohd Sharul Rusyaidi (2018)
The purpose of this study is to investigate the relationship between the four aspects of career growth (Career Goal Progress, Professional Ability Development, Promotion Speed and Remuneration Growth) and organizational commitment. This study was conducted at Pejabat Daerah Samarahan, located in Kota Samarahan,Sarawak. There were 100 questionnaires distributed to 86 respondents and based on the results of 86 respondents, there was a positive correlation coefficient between career growth factors and organizational commitment. There are positive, high and significant relationship between career goal progress and organizational commitment (r=.604**, p>0.01), professional ability development and organizational commitment (r=.524**, p>0.01), promotion speed and organizational commitment (r=.601**, p>0.01), and remuneration growth and organizational commitment (r=.531**, p> 0.01). The positive correlation coefficient indicates that an increase in career growth led to increase in organizational commitment thus indicates employees at this organization are aware of their own long term career plan.